Cardiovascular Risk Assessment Using the Framingham Risk Score in Type 2 Diabetic Population in Nepal: Hospital-Based Study - Joshi, Bishal Raj; Shah, Sonu; Roy, Pratap Kumar; Rizal, Shikha (Nepal Journal of Health Sciences, 2024)
Introduction: There is a growing concern about the link between type 2 diabetes and increased cardiovascular risk in the Nepalese population. There is limited data on the utility of cardiovascular risk assessment tools in our population. This study examines the 10-year risk of cardiovascular events in type 2 diabetic patients in eastern Nepal using the Framingham Risk Score. Objective: The primary objective was to estimate the 10-year risk of coronary heart disease among type 2 diabetic patients using the Framingham Risk Score and categorize these patients into low, moderate, and high-risk groups. <>Methods: A hospital-based cross-sectional study was conducted from April 2023 to March 2024 at Nobel Medical College Teaching Hospital, Biratnagar, Nepal, with ethical approval from the institutional review committee. A total of 225 type 2 diabetic patients aged 30-74 years were enrolled from the medicine out-patient department. Data collected included demographics, clinical measurements (Basal metabolic rate, blood pressure), and biochemical data (fasting blood sugar, postprandial blood sugar, total cholesterol, HDL-cholesterol, and triglycerides). The Framingham Risk Score was used to estimate 10-year cardiovascular risk, categorizing patients into low (<10%), moderate (10-20%), and high (>20%) risk categories. Results: The mean 10-year Cardiovascular risk was 16.01% (95% CI: 14.50 – 17.52), with males showing a significantly higher risk (18.9%) compared to females (11.0%). Risk increased with age, peaking at 22.3% in patients >60 years. Approximately 38.4% of participants were classified as high-risk, with males comprising 51.1% of this group. The average heart age exceeded chronological age by 16.93 years (66.95 vs 50.02 years). Conclusion: This study reveals a substantial 10-year cardiovascular disease risk among type 2 diabetic patients in Nepal, with significant gender differences and increased risk with age. These findings emphasize the need for routine cardiovascular risk assessment and tailored prevention strategies, as well as the validation of risk assessment tools for the Nepalese population.